Rethinking the future low-carbon city: Carbon neutrality, green design, and sustainability tensions in the making of Masdar City - Griffiths, Steven (2020)
As the global trend toward urbanization continues, new models for the design and governance of sustainable cities are being developed. The Abu Dhabi government announced in 2006 its intent to spend $22 billion to build one such city, Masdar City, as a carbon-neutral, zero-waste city that would demonstrate the state-of-the-art in sustainable city design. As initially planned, Masdar City was a bold experiment: an incubator of clean-technologies that was to be powered exclusively by renewable energy while exhibiting the highest levels of energy efficiency. Partly due to the 2008 global financial crisis and partly due to lessons learned from continued assessments of the original concept, planners at Masdar both scaled back initial ambitions for the city's carbon and waste targets and significantly altered both the city's development approach and timeline for completion. This, however, may turn out to be the best outcome for Masdar City if it is truly to become a model for “eco-cities” of the future. Masdar now seeks a more commercial model that nonetheless retains a focus on sustainable urban design. This Perspective reviews the history of Masdar City from its inception to the present day and highlights the major changes that have occurred in its city planning. In consideration of the facts presented, Masdar City may yet emerge as a true eco-city. Regardless, it certainly constitutes an omen with incredibly important empirical lessons for other cities around the world seeking to become more sustainable.